RESPON MASYARAKAT TERHADAP PEMBANGUNANPEMBANGKIT LISTRIK TENAGA MINIHIDRO SANTONG KECAMATAN KAYANGAN LOMBOK UTARA - Subagio, Subagio (Jurnal Ilmiah IKIP Mataram, 2018)
This research purposes to identify society’s social and economic characteristics in building site and to analyze society’s knowledge and response to PLTM and the environment impact it causes.This research is conducted in Santong Village, Kayangan sub district West Lombok district, Nusa Tenggara Barat Province using survey and secondary data analysis. Society’s social and economic characteristics are measured from 119 samples of households about their prosperity, education, age, occupation, land ownership; land width, members of the family and earning per month factors. The respondents are then measured on their knowledge and response to physical, biotic, economic, and social properness and government role in the plan of PLTM Santong construction. Data analysis uses cross tabulation and variance.The result shows that there is no difference n respondents’ social and economic characteristics, especially for age variable which has trust level of 26.29 (F=26.69; sig=29.46 in a 0.05), land width has trust level of 1.14 (F=1.14; sig=29.46 in a 0, 05) and occupation type has trust level of 1.423 (F=1.423; sig=3.00 in a 0.05) which means respondents in the research site have relatively equal age, land width and occupation type. They are dominated by age between 31-47 years old for 53.78 percent and work on agriculture sector for 56.30 percent with land width <100 m2. The difference in respondents’ knowledge of PLTM construction and the impact it causes lies on the middle site which has trust level of 30.21 (F=30.21 ;sig=19.00 in a 0.05) which means respondents in the research site have relatively equal knowledge for 49.58 percent of average knowledge and 47.06 percent of knowledge. It relates to response level of the respondents of PLTM construction and environment impact it causes has the trust level of 105.03 (F=105.03; sig=19.00 in a 0.05). The conclusion is that from 119 heads of household who become the research’s respondents, 94.12 percent of them has positive response level to PLTM construction and environment impact it causes.